2014
DOI: 10.5210/fm.v19i9.5216
|View full text |Cite
|
Sign up to set email alerts
|

A robust gender inference model for online social networks and its application to LinkedIn and Twitter

Abstract: Online social networking services have come to dominate the dot com world: Countless online communities coexist on the social Web. Some typically characteristic user attributes, such as gender, age group, sexual orientation, are not automatically part of the profile information. In some cases user attributes can even be deliberately and maliciously falsified. This paper examines automated inference of gender on online social networks by analyzing written text with a combination of natural language processing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
0
13
0
3
Order By: Relevance
“…The dataset has been used in various subsequent studies (Bergsma and Van Durme 2013;Van Durme 2012;Volkova, Wilson, and Yarowsky 2013). Others created their own Twitter dataset (Eisenstein, Smith, and Xing 2011;Kokkos and Tzouramanis 2014;Liao et al 2014;Rao et al 2010;Zamal, Liu, and Ruths 2012). While early studies focused on English, recent studies have used Twitter data written in other languages as well, like Dutch (Nguyen et al 2013), Spanish and Russian (Volkova, Wilson, and Yarowsky 2013), and Japanese, Indonesian, Turkish, and French (Ciot, Sonderegger, and Ruths 2013).…”
Section: Data Sourcesmentioning
confidence: 99%
“…The dataset has been used in various subsequent studies (Bergsma and Van Durme 2013;Van Durme 2012;Volkova, Wilson, and Yarowsky 2013). Others created their own Twitter dataset (Eisenstein, Smith, and Xing 2011;Kokkos and Tzouramanis 2014;Liao et al 2014;Rao et al 2010;Zamal, Liu, and Ruths 2012). While early studies focused on English, recent studies have used Twitter data written in other languages as well, like Dutch (Nguyen et al 2013), Spanish and Russian (Volkova, Wilson, and Yarowsky 2013), and Japanese, Indonesian, Turkish, and French (Ciot, Sonderegger, and Ruths 2013).…”
Section: Data Sourcesmentioning
confidence: 99%
“…For example, Felbo et al and Sarraute et al predict the gender with respectively 79.7% and 77.1% 3 accuracy, either by harnessing their temporal information using deep learning or by using linear SVM and logistic regression [5], [26]. Other works tackle the gender prediction problem in a similar way using different kinds of data sets, such as Twitter or LinkedIn data, the first name of a person or even chat texts [31]- [33]. Closer to our work, Al Zamal et al exploit the homophily in a Twitter network to predict the users' gender, age, and political affiliation [2], by analyzing how the knowledge of the data from some immediate friends of a given user can improve the prediction quality.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown how valuable the social science lens is to computational fields (Kokkos & Tzouramanis, 2014;Nguyen, Doğruöz, Rosé, & de Jong, 2016;Otterbacher, 2013). Researchers at this intersection are aware of the tension between the theoretical framing and empirical methods of their work.…”
Section: Unlikely Alliesmentioning
confidence: 99%